Inferior mesenteric vein thrombosis in the setting of testosterone therapy. Issue 12 (14th December 2022) - Manongi, Ngoda; Byrns, Kory; Fulman, Malvina; Jaffer, Amir
Abstract : Inferior mesenteric vein thrombosis (IMVT) is a rare and potentially lethal complication that can progress to mesenteric ischaemia if left untreated. We report a case of a man in his 70s with a history of polycythaemia vera (PV) with a known negative Janus kinase-2 mutation ( JAK2V617 ) who was started on testosterone therapy 2 months before presenting with left lower quadrant abdominal and flank pain. Evaluation revealed thrombocytosis and IMVT on CT scan. A non-operative approach was deferred for anticoagulation therapy. Within 24 hours, the patient demonstrated significant clinical improvement, and he subsequently made a full recovery. The patient underwent 6 months of anticoagulation therapy with Apixaban. This case documents the first case of IMVT in the setting of PV and testosterone therapy in the literature.